Effects of team-skills guidance on accounting students with lone wolf tendencies - SEOW, Jean Lin (Institutional Knowledge at Singapore Management University, 2018)
We investigate whether short-term in-class team-skills guidance impacts the perceptions of accounting students with lone wolf tendencies on team work, and peer evaluation systems adopted in team work. We find that students with greater lone wolf tendencies see fewer benefits from engaging in team work, believing this to result in a poorer learning experience and poorer team performance outcomes. They are also less flexible in thought and feel more incompetent working in teams, preferring to rely on self and to work on their own. Unlike students with lesser lone wolf tendencies, they are also less comfortable with peer evaluation systems, being less convinced that peers are able to evaluate each other fairly. In terms of team-skills guidance, we find that students who are exposed to this are more aware of shortcomings in their teams, in terms of how well they work together, as well as in the performance outcomes. Team-skills guidance also leads students to be more concerned about there being collusion in peer evaluation ratings, and thus, being less satisfied with the peer evaluation process used in our study. In terms of interaction effects, we find that the specific form of team-skills guidance explored in our study results in students with greater lone wolf tendencies perceiving one positive benefit from engaging in team work: they find working on the project to be easier than students not exposed to this team-skills guidance. Students with greater lone wolf tendencies who undergo team-skills guidance are also more concerned that friendship and popularity may distort the reliability of peer evaluation. Among students with lesser lone wolf tendencies, we find that team-skills guidance results in the perception of fewer benefits from engaging in team work on a number of dimensions when compared to students not exposed to team-skills guidance.